Saff-Chol Juice: Your Healthy Drink - Mohd Kasim, Noor Alicezah; Abd Rahim, Iman Nabilah; Mohd Nawawi, Hapizah (2020)
Atherosclerosis has been established to be an indolent inflammatory disease of the arteries which can gives rise to coronary artery disease (CAD), one of the most prevalent causes of death in developed and developing countries. Saffron, one of the world’s most expensive spices, is collected from dried stigmas of Crocus sativus L. Saffron exhibits favourable effects in the prevention or treatment of a variety of diseases including dyslipidemia, hypertension and diabetes mellitus. Our previous in-vitro work showed that Saffron downregulates gene and protein expressions of inflammation, endothelial activation and upregulate the gene of oxidative stress and inhibit monocyte- endothelial interactions which are the key events in pathogenesis of atherosclerosis. Thus, we have translated our research finding into saffron formulated drink; Saff-Chol Juice. It can be used as daily healthy drink to combat many atherosclerosis complications such as heart attack, stroke and renal failure. It is safe and easy to consume. This product may benefit patients with heart problem, hypertension and renal failure. It is also useful for smokers who is at risk to develop atherosclerosis.